Interannual variability of water masses in the area of bottom water formation in Рrydz Вay - N. N. Antipov; A. V. Klepikov; Н. Н. Антипов; А. В. Клепиков (Arctic and Antarctic Research, 2017)
The results of field studies of the processes of Antarctic Bottom Water formation conducted in the period from 2004 to 2016 in the Prydz Bay of the Commonwealth Sea is discussed. During this period the oceanographic observations along the 70° E section, crossing the shelf and the continental slope, were repeated nine times. In this area in the austral summer of 2004 during the AARI expedition on the r/v “Akademik Fedorov” the process of formation of bottom water has been recorded for the first time. A further study of the structure and characteristics of water masses on this section and in the adjacent area confirmed the regularity of these processes during the summer period. At the same time, a significant interannual variability of the structure, characteristics, and mechanisms of distribution of the main water masses in the section shelf, deep and bottom waters — was found. For the first time, detailed information on the bottom topography of the ocean in the vicinity of this section made it possible to show the determining role of bottom topography features in the distribution of newly formed bottom water along the continental slope. The tendency of increasing of the volume of bottom water formed in the Prydz Bay in recent years is revealed, which is associated with the intensification of the basal melting of the ice shelf leading to an increase in the volume of the formation of supercooled Shelf Water, the most important component in the formation of bottom water. В работе обсуждаются результаты экспедиционных исследований процессов формирования антарктической донной воды, проведенных в период с 2004 по 2016 г. в заливе Прюдс моря Содружества. Анализируются данные океанологических наблюдений на разрезе по 70° в.д., выполненном за указанный период девять раз и пересекающем шельф и материковый склон в районе, где в летний период 2004 г. экспедиция ААНИИ на НЭС «Академик Федоров» впервые зафиксировала факт формирования донных вод. Дальнейшее целенаправленное исследование структуры и характеристик водных масс ...